Government Collaboration in Enhancing National Defense - Eko Sugiarto; Lalu Pardede Gita Prahara; Atep Priatna; Rizky Mugia Priatna (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2024)
Security dynamics in the Southeast Asian region have increased, influenced by many factors, ranging from internal member states, regional situations, to security dynamics in the Asia Pacific region and beyond. This article will review the security conditions of the ASEAN region through a government collaboration literature study approach. As a result, the implementation of joint military exercises of ASEAN countries plays an important role in creating regional security. There are at least several benefits obtained: First, joint military exercises can improve state defense capabilities and regional security. Second, through joint exercises, the forces of ASEAN countries will be better prepared and able to respond to any threats that disrupt regional security and sovereignty. Third, joint military exercises provide a space for productive discussions and consultations to discuss the security situation of member states and the Southeast Asian region, resulting in a common formula in maintaining regional security. Fourth, joint military exercises can serve as a mediation platform for ASEAN countries in conflict with other ASEAN countries to find a constructive middle ground for regional security stability